In-silico Approach for The Prediction of Chlorogenic Acid as PPAR-γ Activator - Yohanes Bare; Mansur S; Sukarman Hadi Jaya Putra; Margaretha Rika W G L; Dewi Ratih Tirto Sari (Biota, 2020)
Coffee is one of the essential crops commonly cultivated in Indonesia. Coffee contains diverse bioactive compounds, which are associated with human health benefits. One of the compounds is Chlorogenic acid, which able to decrease the risk of type 2 diabetes mellitus (T2DM). However, the mechanism of chlorogenic acid toward anti-diabetes still unclear. This study aimed to analyze and investigate the potential role of chlorogenic acid as anti-diabetes through their interaction with Peroxisome proliferator-activated receptor gamma (PPAR-γ) as an enzyme to phosphorylate and regulate the mechanism of T2DM. The physicochemical properties of chlorogenic acid also performed in this study. The PPAR-γ was downloaded from the PDB database, and the chlorogenic acid was retrieved from the PubChem database. The protein and ligand were prepared using the PyRx program and were docked using Hex 8.0.0 software. Discovery Studio client 4.1 software was used to analyze the interaction between chlorogenic acid and PPAR-γ protein. Based on the physicochemical properties, chlorogenic acid is highly permeable to the cell and easily absorbed. Thirteen amino acid residues of PPAR-γ (GLN410, SER394, ASP396, GLY395, GLU407, LEUA401, LEU400, VAL403, LYS373, LYS438, LEU377, LYS434, and GLY437) were identified on the chlorogenic acid-PPAR-γ interaction. Interestingly, the kind of interactions, including hydrophobic interaction, hydrogen bond, and van der Waals, which are supported by the tight interaction. Our study indicated that chlorogenic acid might have anti-diabetes activity through PPAR-γ interaction.